Management of Diabetic Neuropathy: A Comparison of Duloxetine with Amitriptyline - Salman Azhar, Nargis Tasleem, Asad Mahmood Khan, Farasat Ali, Saima Tabassum (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the pain-relieving effects of duloxetine vs those of amitriptyline in the treatment of diabetic neuropathy. Methodology: In this randomized trial control, 150 cases of diabetic neuropathy by using convenient sampling technique from Medical Department of Madinah Teaching Hospital, Faisalabad were enrolled and divided in 2 equal groups randomly. Group A was assigned to (Duloxetine) and B assigned to (Amitriptyline). Patients received the trial drug in the morning with water for 6 weeks. Group A got 60 mg of Duloxetine and Group B 75 mg of amitriptyline. VAS pain rating. Patient consultations included a diary card. Patients recorded daily improvements on a visual analogue scale for the first three weeks. We administered three weeks of medicine and arranged an examination in week 6. When pain levels were 50% lower than baseline, we rated them as reduced. Patients were phoned. Results: The mean age was 46.19+6.39 years. 41(54.67%) of Group-A and 39(52%) of Group-B were male, whereas 34(45.33%) and 36(48%) were female. Both groups’ mean VAS pain ratings were 1.48+0.50; p = 0.746 shows no difference. Group-A (0.48+0.50) and Group-B (0.92+0.69) vary significantly (p=0.0001). Group-A (52%) and Group-B (28%) were effectively treated after 6 weeks, p=0.002. Conclusion: Our research shows that duloxetine is superior to amitriptyline for the management of diabetic neuropathy, especially in terms of minimising the frequency with which patients report experiencing pain. Keywords: Diabetic neuropathy, management, duloxetine, amitriptyline, efficacy